EÇA DE QUEIRÓS E MACHADO DE ASSIS: CRONACA DI UN MANCATO INCONTRO - DE OLIVEIRA, Vera Lúcia (Studia Universitatis Babeș-Bolyai Philologia, 2017)
Eça de Queirós and Machado de Assis: a chronicle of a missed encounter. Eça de Queirós and Machado de Assis had much in common, just as so many are the differences that separate them, both in the conception of the world and of art. Machado never left Rio de Janeiro and his trips were vertical, in the consciousness of the fictional characters and of his time. Eça, on the other hand, was a restless traveler, and from 1872 on, he almost always lived outside Portugal. From this perspective, he made a kind of autopsy of the Portuguese society of that time, with a refined and ironic language. In this work, I have tried to trace the lines of a subtlety dialogue between these two great writers, a possible encounter that for various reasons, never really happened. Rezumat. Eça de Queirós și Machado de Assis: cronica unei întâlniri ce nu a avut loc. Eça de Queirós și Machado de Assis au multe în comun, așa cum multe sunt și diferențele care îi despart, atât în ceea ce privește viziunea asupra lumii, cât și concepția asupra artei. Machado nu a plecat niciodată din Rio de Janeiro, iar călătoriile lui au fost verticale, în conștiința personalelor ficționale și în cea a vremurilor sale. Eça, pe de altă parte, a fost un călător neobosit, din 1872 locuind aproape numai în afara Portugaliei. Din această perspectivă, a realizat un fel de autopsie a societății portugheze din vremea respectivă, folosind un limbaj rafinat și ironic. În această lucrare, am încercat să creionez un subtil dialog între cei doi mari scriitori, o întâlnire posibilă care, de fapt, din diferite motive, nu a avut loc niciodată. Cuvinte cheie: Eça de Queirós, Machado de Assis, literatură portugheză, literatură braziliană, realism